Implementation of Islamic Religious Education Teachers’ Professional Ethics in Fostering Students’ Moral Character Development - Abd. Mukhid; Tri Setiawati; Biwi Nazma Rabbania; Aprillia Dwi Lestari Ananta; Fahmi Fahrezi (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The purpose of this study was to examine the influence of the professional ethics of Islamic Religious Education (IRE) teachers on students’ morality at SDN Panglegur 2, Pamekasan, and to identify supporting and inhibiting factors in the implementation of IRE. This qualitative study employed observations, interviews, and document analysis to collect data from IRE teachers and students. Data validity was ensured through triangulation techniques. The findings reveal that IRE teachers function not only as educators but also as role models who demonstrate positive attitudes and behaviors in daily interactions. The implementation of professional ethics is reflected in teachers’ discipline, responsibility, exemplary conduct, and effective communication skills. These ethical qualities contribute positively to students’ moral development by enhancing discipline, politeness, learning motivation, and cooperative attitudes. In addition, teacher involvement, a supportive school environment, and consistent school routines strengthen the internalization of positive values among students. Nevertheless, several challenges remain, including students’ diverse backgrounds, limited self-confidence among some learners, and restricted instructional time. Therefore, the consistent application of professional ethics by IRE teachers is essential for fostering students’ moral growth and should be continuously supported to achieve optimal educational outcomes.